2017
DOI: 10.1007/s11356-017-9513-4
|View full text |Cite
|
Sign up to set email alerts
|

First detection of enteric adenoviruses genotype 41 in recreation spring areas of Taiwan

Abstract: Human adenoviruses (HAdVs) are DNA viruses found in recreational water, such as water parks and swimming pools. Human adenovirus 41 (HAdV-41) is the most common serotype detected and is a leading cause of acute diarrheal disease. The focus of this study is to determine the prevalence of HAdVs in hot springs. Of 57 samples collected from four different geological sites, 16 samples have shown evidence of HAdVs (28.1%). HAdV-41 and porcine adenovirus 5 (PAdV-5) were the two types isolated, with a greater frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The present review identified six published studies reporting the viruses’ detection in swimming pool waters in tropical countries [114,115,116,117,118,119] (Table 2). The earliest was a study of a primary school outbreak of pharyngoconjunctival fever attributed to swimming in the swimming pool of a school camp [114].…”
Section: Resultsmentioning
confidence: 99%
“…The present review identified six published studies reporting the viruses’ detection in swimming pool waters in tropical countries [114,115,116,117,118,119] (Table 2). The earliest was a study of a primary school outbreak of pharyngoconjunctival fever attributed to swimming in the swimming pool of a school camp [114].…”
Section: Resultsmentioning
confidence: 99%
“…HAdV41 represented 12 to 77% of overall HAdVs in lake samples collected at recreational beaches in the USA (Xagoraraki et al 2007). The frequent presence of HAdV41 in recreational hot springs in Taiwan has also been recently described (Shih et al 2017).…”
Section: Introductionmentioning
confidence: 84%
“…Human adenoviruses (HAdV) are DNA viruses found in recreational waters. Human adenovirus 41 (HAdV-41) is the most common serotype detected and is a leading cause of acute diarrheal disease [32].…”
Section: Viruses A) Adenovirusesmentioning
confidence: 99%
“…A study conducted in the hot spring areas of Taiwan found that the highest prevalence of HAdVs was in the public area and bathing in hot spring facilities. Of the 57 samples modified in the study from four different geological sites, 16 samples (28.1%) contained HAdV-41 [32].…”
Section: Viruses A) Adenovirusesmentioning
confidence: 99%